Working Toward Becoming Doctoral Researchers: A Collective Autoethnography of International Students in Australia - Lin, Yuqi; Shi, Jing; Zhang, Chenyang (Journal of International Students, 2022)
It is well established that international education can profoundly influence a student, including identity and agency formation and the acquisition of knowledge and culture. This study applies the concept of self-formation to reconceptualize the international student experience. It captures the development, changes, and operation of identity and agency during self-formation. Utilizing collective autoethnography, the authentic experiences of three international students studying in Australia during the Covid-19 pandemic were collected. These stories illustrate their transformation from international students to student researchers. Through thematic analysis, three phases have been identified in this study, which are self-exploration, self-positioning, and self-determination and shedding light on the role of agency and hybrid identity. A further scholarly investigation is advocated to enrich the discussion of self-formation and add a nuanced investigation into the variability of individual experiences.